Neurofeedback and mental health: An integrative research agenda - Ahmad, Zainal Ariffin (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
This is a two-part study to investigate mental health from two perspectives, namely counseling and neuroscience. The objective of the first part of the study is how to assess the state of mental health and assist individuals in dealing with mental issues as a primary intervention. This objective wa accomplished by adopting the Mental Health Facilitator program under NBCCI. In line with USM's effo to have a cadre of mentors in the university, a group of 18 volunteers consisting USM academic and administrative staff underwent 45-hour training and certified as Mental Health Facilitators (MHF) by tw trainers from the National Board of Certified Counselors International (NBCCI). USM is the first universit in the world to train its employees to become Mental Health Facilitators. The MHF certification is valid for years (2008-2010) and the MHFs have to participate in continuing education programmes. Several of th MHFs then became trainers for subsequent batches of USM Mentors in 2009 and 2010 with a total of 49 throughout the three campuses. In 2010, four of the MHFs trainers were further certified by NBCCI a Master Trainers, the only ones certified to train in Southeast Asia. Concurrent with the MHF training, the objective of the second part of the study is to establish the protocol, process and procedures for conducting EEG and neurofeeback research for non-medica researchers. This objective was accomplished by following the EEG procedure and protocol from EGI. The researchers purchased a EEG 300 System with NetStation and E-Prime. Using 32 Channel Hydroce Nets, data was gathered from volunteers on several experiments. Two separate experiments by the Ph candidates were the thinking styles of school children and decision making style of managers. However, the two experiments were not able to be completed due to malfunction of the EEG software until the end of grant term. However, the researchers involved presented papers in Australia and Japan and were afforded training in the United States-EGI Summer School for EEG in Eugene, Oregon (July 2oog) and BESA Workshop in San Diego, California (November 2010). Notably, our PhD candidate received scholarship to attend and present the Neuroleadership Conference in Boston, MA in October 2010 and to be published in the Neuroleadership Journal.